MODELS OF TEACHING PEDAGOGICAL SUBJECTS IN THE CONDITIONS OF GLOBALIZATION (American Journal of Pedagogical and Educational Research, 2024)
This article presents an opinion on today's modern models of teaching pedagogical subjects in the conditions of glocalization and their specific capabilities. Research in modern education suggests new models of vocational education and training. This situation also requires teachers to constantly resort to new approaches in their professional activities.